IMPLEMENTATION OF THE POLICY ON THE INFLUENCE OF PAPUA PROVINCE'S SPECIAL ALLOWANCE ON THE PERFORMANCE OF TNI-AD SOLDIERS/CIVIL SERVANTS IN THE OPERATIONAL AREA: Implementasi Kebijakan Pengaruh Tunjangan Khusus Provinsi Papua Terhadap Kinerja Prajurit/PNS TNI AD Di Daerah Operasi - Priyanto; Sigit Purwanto; eko setya budi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This research examines the influence of the Papua Province Special Allowance on the performance of TNI AD soldiers and civil servants in the operational area. A quantitative approach was used with a questionnaire survey distributed to respondents in Papua Province. Data were analyzed through linear regression and mediation analysis to assess the direct impact and role of mediating variables such as job satisfaction and Organizational Citizenship Behavior (OCB). The results show that Special Allowances have a significant positive effect (p < 0.05) on performance by increasing motivation, effectiveness and productivity. In addition, the job satisfaction and OCB variables were proven to be significant as mediators, strengthening the relationship between benefits and performance. Based on these findings, the research recommends periodic evaluation of allowance policies, development of more comprehensive welfare programs, and improvement of operational facilities and ongoing training for soldiers and civil servants in strategic operational areas such as Papua.